Response of Sorghum [Sorghum bicolor(L.) Moench] to Phosphorus and Nitrogen Fertilization under Rainfed Conditions, Blue Nile State – Sudan* - El Mahi, Yousif E.; Salih, Tarig M. N. (University of Khartoum Journal of Agricultural Sciences, 2023)
Two field experiments were conducted on a Typic chromusterts, fine, smectitic, isohyperthermic soil series in the Damazin Research Station farm during two seasons (2005/06 and 2006/07). The objective was to investigate the effect of phosphorus (P) and nitrogen (N) and their interactions on sorghum [Sorghum bicolor (L.) Moench] growth and grain yield. A randomized complete block design with four replicates was used to execute the experiments. Plant height, grain yield and dry matter were significantly increased by N and P applications, in both seasons.The average yield of sorghum grain in the two seasons was 0.6 tons ha-1 for the control and 4.4 tons ha-1 for the highest fertilizer treatment (P 80 N80 ). There were mutually synergistic effects between N and P which significantly (P<0.0001) promoted growth and yield of sorghum. Phosphorus enhanced nitrogen uptake and nitrogen use efficiency and vice versa. At all N applications, phosphorus use efficiency tended to decrease with increase in the rate of P application. The highly significant response of sorghum to P and N fertilizers warrant recommending their application under the rainfed conditions of Damazin, Sudan.